Psychoeducational action plan for the establishment of performance goals in the volleyball team of the Bayamo Faculty of Medical Sciences (Original) (Revista científica Olimpia, 2020)
The present investigation contributes a plan of psychoeducational actions that will contribute to the correct establishment of performance goals by the teacher in the different stages of the macrocycle. For this, a sample of 20 volleyball players from the Bayamo Faculty of Medical Sciences, the provincial Methodologist, coach and 9 sports specialists are taken. In order to solve the problem posed, the theoretical analytical - synthetic, logical historical, deductive inductive and functional structural systemic methods were used and as empirical methods document analysis, interview and survey; and psychological tests, the descriptive statistics and the SPSS version 11.5 statistical package were used to analyze the data obtained. The results obtained revert to achieving greater motivation in the coach and practitioners in group work as a team, development of group work skills, improvement of goal-setting work in team leadership and team orientation. the ideals and aspirations of goals and a better preparation of the practitioners for another superior stage of their sports life.
Keywords: psychoeducational actions; goals; medical sciences; goal setting; sport.